Comparison Analysis Of Sharia Financial Technology With Conventional Financial Technology In Indonesia - Suciati, Rahma; Setiawan, Deny; Misdawita, Misdawita (Jurnal Ilmiah Ekonomi Islam, 2024)
According to national digital research center (NDRC), financial technology describe innovation in field finance with use technology latest. As institution finance, financial technology must guard performance so that can operate with optimal. The purpose of this study is to compare the financial performance of sharia financial technology with conventional financial technology in Indonesia in 2021 and 2022 using ROA, ROE, TKB90, and TWP90. The analysis technique used in this study is the independent sample t-test. The results of this study indicate that there is no significant difference between the ROA and ROE of sharia financial technology and conventional financial technology. Whereas TKB90 and TWP90 sharia financial technology and conventional financial technology there are significant differences, where sharia financial technology has better quality than conventional financial technology.